Konsep 4R Sebagai Moderasi Pengaruh Gamifikasi Terhadap Niat Membeli Kembali dan Pengalaman Merek Konsumen Shopee - Nugraha, Andhyka Tyaz; Puspitawati, Ni Made Ratih; Fathurochman, Alam (Jurnal Bisnis dan Kewirausahaan, 2024)
This article aims to fill the research gap related to marketplaces digital marketing mix by using elements of gamification to consumers. The problem is focused on identifying the effect of gamification on brand experience without and with moderation of the 4R Concept as well as the effect of brand experience on consumer repurchase intention in the Shopee marketplace. Data collection was carried out by purposive sampling through online questionnaires with a Likert scale of 5. Data processing was carried out on 85 respondent data using SmartPLS software with the PLS-SEM approach. The results of this research data processing are first, the application of gamification elements into the marketplace can improve consumer brand experiences. Second, the effect of gamification on consumer brand experiences can be enhanced by the 4R Concept. Finally, brand experience influences consumer purchase intentions towards the marketplace. The conclusion obtained is that the brand experience of marketplace consumers can be improved either by simply incorporating elements of gamification or with the help of the 4R Concept. Then, brand experience can increase consumer interest in making repeat digital transactions on the marketplace